2022
DOI: 10.1177/17474930211064076
|View full text |Cite
|
Sign up to set email alerts
|

J-shape relation of blood pressure reduction and outcome in acute intracerebral hemorrhage: A pooled analysis of INTERACT2 and ATACH-II individual participant data

Abstract: Objective: The aim of this study was to better define the shape of association between the degree (“magnitude”) of early (< 1 h) reduction in systolic blood pressure (SBP) and outcomes in patients with acute intracerebral hemorrhage (ICH) through pooled analysis of the second Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial (INTERACT2) and second Antihypertensive Treatment of Acute Cerebral Hemorrhage (ATACH-II) datasets. Methods: Association of the continuous magnitude of SBP reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Despite this, two large randomized trials, INTERACT2 and ATACH-II, comparing BP goals of less than 140 mmHg to less than 180 mmHg, have failed to show mortality or functional benefit [41,42]. A recent meta-analysis of both of these trials, however, found a J-shaped curve, with an inflexion point and improved functional outcomes when SBP was reduced between 32 and 46 mmHg within the first hour and worse functional outcomes when SBP was reduced over 60 mmHg [43 ▪▪ ]. Thus similar to findings of BP reduction post mechanical thrombectomy, there appears to be a benefit with modest lowering and harm at greater amounts.…”
Section: Intracranial Hemorrhagementioning
confidence: 99%
“…Despite this, two large randomized trials, INTERACT2 and ATACH-II, comparing BP goals of less than 140 mmHg to less than 180 mmHg, have failed to show mortality or functional benefit [41,42]. A recent meta-analysis of both of these trials, however, found a J-shaped curve, with an inflexion point and improved functional outcomes when SBP was reduced between 32 and 46 mmHg within the first hour and worse functional outcomes when SBP was reduced over 60 mmHg [43 ▪▪ ]. Thus similar to findings of BP reduction post mechanical thrombectomy, there appears to be a benefit with modest lowering and harm at greater amounts.…”
Section: Intracranial Hemorrhagementioning
confidence: 99%
“…This led to the development of a progressive activity algorithm used in the neurocritically ill population and providing safety boundaries for this progression 31 . Using this approach, we have successfully implemented progressive verticalization to safely introduce high-intensity recovery activities in a population of patients prone to autonomic dysfunction 32–34 …”
Section: The Opportunity: System Redesignmentioning
confidence: 99%
“…31 Using this approach, we have successfully implemented progressive verticalization to safely introduce high-intensity recovery activities in a population of patients prone to autonomic dysfunction. [32][33][34] Intracranial hypertension is another safety issue for consideration in increasing early activity protocols for hospitalized patients with both ischemic and hemorrhagic stroke. Therefore, attention to this physiological variable when considering the addition of high-intensity activity is essential.…”
Section: Patient Stratificationmentioning
confidence: 99%
“…44 Secondary analysis of ATACH-II indicates adverse events were more frequent in patients in the intensive arm who had their SBP reduced from ≥220 mm Hg to <140 mm Hg, 45 which has been supported by further analysis of the pooled dataset showing an increase in adverse outcomes with a large magnitude of SBP lowering (>60 mm Hg within 1 hour). 46 Most patients who were included in both these RCTs had deep ICH, but the response to BP lowering may differ by location of the hematoma. 47…”
Section: Bp and Acute Ich And Subsequent Adverse Outcomesmentioning
confidence: 99%